Public Inputs as Signalling Devices - Gianluca Fiorentini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
A two stage model is built where the first period strategic variable is used to update the information available on some private characteristics of the rival firms.
Keywords: 330